2008
DOI: 10.1021/es703213p
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method for Enhancing the Destruction of Environmental Pollutants by the Combination of Multiple Plasma Discharges

Abstract: A novel, multistage, dielectric, packed-bed, plasma reactor has been developed and is used to efficiently destroy environmental pollutants, such as volatile organic compounds (VOCs). A three cell plasma reactor, operated at ambient pressure and low temperatures, is found to be an effective technology for complete VOC remediation in air. The combination of plasma cells in series can significantly improve the efficiency of VOC decomposition, but the combined destruction rate is not simply an additive effect, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 28 publications
(41 reference statements)
4
59
0
Order By: Relevance
“…This is because when multiple discharge chambers are operated with gas flow in series, some of the reactive species formed in the previous discharge chamber survive long enough and have a synergistic effect on the plasma/chemical reactions. So, the combined reaction rates in multiple discharge chambers in series are not a simple addition, there is synergistic enhancement, which is in agreement with earlier literature [33].…”
Section: Discussionsupporting
confidence: 92%
“…This is because when multiple discharge chambers are operated with gas flow in series, some of the reactive species formed in the previous discharge chamber survive long enough and have a synergistic effect on the plasma/chemical reactions. So, the combined reaction rates in multiple discharge chambers in series are not a simple addition, there is synergistic enhancement, which is in agreement with earlier literature [33].…”
Section: Discussionsupporting
confidence: 92%
“…Non-thermal plasma technology has been regarded as a promising alternative to the thermal catalytic route for converting low value and inert carbon emissions, such as CH 4 and CO 2 , into value-added fuels and chemicals at atmospheric pressure due to its non-equilibrium characteristic, low energy cost and unique capability to induce both physical and chemical reactions at ambient conditions. [5][6][7] In non-thermal plasmas, the overall plasma gas temperature can be as low as room temperature, while the electrons are highly energetic with an average electron energy of 1-10 eV which can easily break down most chemical bonds of inert molecules and produce chemically reactive species such as radicals, excited atoms, molecules, and ions for chemical reactions. The non-equilibrium character of such plasmas could enable thermodynamically unfavorable reactions (e.g., CO 2 splitting) to occur at low temperatures (e.g., <200 8C).…”
Section: Introductionmentioning
confidence: 99%
“…The synergy of NTP and heterogeneous catalysis (NTP-C) is a promising technology for VOC removal at ambient temperature. Researchers have reported that the NTP-C composite process can greatly reduce the energy consumption, save cost, and improve the biodegradation efficiency (Harling et al 2008;Gerasimov 2007;Chen et al 2009). Specially, the quantities of reaction by-products such as aerosols, ozone, and smaller organic compounds are also significantly reduced over NTP-C system (Kim et al 2005a, b).…”
Section: Introductionmentioning
confidence: 99%